Financial State-owned Enterprises’Risk Information and Market Value In China - PENG, ZUNCHENG (2017)
Risk information and market value are perceived to be very important aspects in a company. This goes beyond the corporate levels into a country’s macro-economic influence. This study was based on the different Financial State-owned Enterprises on their Risk Information and their respective Market Value in China. The project was mainly aimed at determining how the published risk information of financial SOEs affects the firm’s market values, with the extent of the effects also considered. This is based on the different state-owned enterprises in China. This was mainly considering if the risk factors negatively or positively affected performance of the selected firms. The data used in this study was mainly mined from individual company financial books for analysis, dividing China into four strata, A Shares Shanghai, A shares Shenzhen, A Shanghai and B Shenzhen. The data collected was mined in Ms. Excel and analyzed in SPSS. The analysis was mainly based on the regression model of the performance and the risk information constituting the model. In A shares Shanghai, risk information was seen to influence performance of a firm. This implied both positive and the negative effects received by the firms in this area. A shares Shenzhen, A Shanghai and B Shenzhen on the other hand indicated that the risk information was not seen to affect the market value at any given point in time. This showed that risk information in this area was not an important factor affecting firms’ performance based on market value. The study is seen to help A shares Shenzhen, A Shanghai and B Shenzhen areas of China look into other factors that may be seen to influence performance, as opposed to the risk information, to ensure the firms enhance better performance over time. This is very important to the Chinese planning department in enhancing corporate development.